BIMBINGAN DAKWAH SAFARI RAMADHAN SANTRI PONPES HIDAYATUL MUBTADIIN GEMEKAN MOJOKERTO UNTUK PENINGKATAN PEMAHAMAN AGAMA DI MASYARAKAT - Moh. Muntholib; Eli Masnawati (AlMurtado Journal of Social Innovation and Community Service, 2025)
This research aims to evaluate the effectiveness of the Ramadhan Safari da'wah guidance program carried out by the students of Hidayatul Mubtadiin Islamic Boarding School in Gemekan, Mojokerto, in enhancing religious understanding within the local community. By using a qualitative research approach, data were gathered through observation, interviews, and documentation. The findings indicate that the Ramadhan Safari program has had a significant positive impact on the increase of religious knowledge, the improvement of worship practices, and the enhancement of moral awareness among community members. Key factors contributing to the success of this program include the well-prepared and relevant religious material provided by the students, which aligns with the needs of the community. The interactive and engaging methods of delivery, such as group discussions, Q&A sessions, and practical guidance, also helped maintain the attention and participation of the audience. Moreover, the active support from the Islamic boarding school’s management, local religious leaders, and community figures played a crucial role in ensuring the program’s success. Their collaboration facilitated a smooth and effective dissemination of knowledge. Ultimately, this research demonstrates that such initiatives can significantly contribute to improving religious understanding and moral development in the community, especially during the holy month of Ramadhan.